2016
DOI: 10.17268/sci.agropecu.2016.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Compost and humic substance effects on soil parameters of Vitis vinifera L cv Thompson seedless

Abstract: The use of organic amendments is common under the concept of integrated nutrient management (INM) in Vitis vinifera (Table grape) -1 and 9.1 µg de TFP g -1 24h -1 , respectively. In addition, pH was similar in all treatments while electrical conductivity increased with application of mineral and organic amendments, reaching 0.41dS m -1 in T2 (HS+MF). Furthermore, yeast concentration increased with organic amendments or mineral. Correlation analysis indicated significant and positive relationships between PO4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…The hydroxyl acids, produced by these bacteria, can be complexed with calcium and increase the availbility of phosphorous as well as reduce soil pH due to substitution of negatively charged organic acids of phosphorus associated with minerals and oxides which leads to the release of phosphorus into the soil solution. These results agreed with Fincheira-Robles et al (2016) and Amruth et al (2017).…”
Section: Shoot Dry Weight (G/pot)supporting
confidence: 88%
“…The hydroxyl acids, produced by these bacteria, can be complexed with calcium and increase the availbility of phosphorous as well as reduce soil pH due to substitution of negatively charged organic acids of phosphorus associated with minerals and oxides which leads to the release of phosphorus into the soil solution. These results agreed with Fincheira-Robles et al (2016) and Amruth et al (2017).…”
Section: Shoot Dry Weight (G/pot)supporting
confidence: 88%
“…According to the above-mentioned results, compost could be an economic and ecologic alternative to improve soil characteristics to induce plant growth promotion (Heargreaves et al, 2008;Fincheira-Robles et al, 2016). Composted grape showed that grape marc compost provided some benefit in returning nutrients into the vineyard.…”
Section: Discussionmentioning
confidence: 98%
“…Orchards are commonly fertilized with NPK and micronutrients sources (Sierra, 2001). Nevertheless, soil agronomic management has been focused on organic matter to improve soil organic carbon (SOC), chemical-physical conditions, and water content in the root zone (Fincheira-Robles et al, 2016;Gaiotti et al, 2016). Commercial products based on humic and fulvic acids are available.…”
Section: Journal Of Soilmentioning
confidence: 99%
“…The quality of the final product, in terms of, e.g., C/N (in the range of 32-45, [27]) and the humification index (in terms of the humic-to-fulvic-acids ratio, equal to 0.9, [25]) was reported to be comparable to that obtainable from other organic substrates, but with a higher calcium content due to the winemaking conditions [28]. Composted pomace was proven to foster the physical, chemical, and biological properties of soils [29]. Studies performed by Ferrer et al (2001) highlighted the positive effects achievable for maize seed germination in greenhouses by using 1-4 ton/ha of compost from pomace [30], and Gaiotti et al (2016) reported that pomace compost was effective in returning nutrients to vineyard soils [31].…”
Section: Introductionmentioning
confidence: 99%